Occupant satisfaction with the indoor environment in seven commercial buildings in Singapore. (15th January 2021) - Cheung, Toby; Schiavon, Stefano; Graham, Lindsay T.; Tham, Kwok Wai
Abstract: Understanding occupants' satisfaction with their environment is an important step to improve indoor environmental quality (IEQ). These satisfaction data are limited to Singaporean commercial buildings. We surveyed (N = 666) occupant satisfaction with 18 IEQ parameters in seven Green Mark certified air-conditioned commercial buildings in Singapore. About 78% of the participants expressed satisfaction with their overall workspace environment. Occupants were most satisfied with flexibility of dress code (86% satisfaction), electrical lighting (84%) and cleanliness (82%), and most dissatisfied with sound privacy (42% dissatisfaction), personal control (32%) and temperature (30%). We found that satisfaction with cleanliness has the highest impact to overall workspace environment satisfaction. Our results suggest achieving high occupant satisfaction for some IEQ factors is harder than others, which suggests the premise of singular satisfaction rating (e.g., 80%) that applies to all IEQ parameters may not be reliable and representative. We determined that the major contributors to thermal dissatisfaction were insufficient air movement and overcooled workspaces. Occupants in open plan office were unhappy with the noise produced by their nearby colleagues. We also found that several IEQ variables (odors, air movement, available space, overall privacy, sound privacy and temperature) which are not statistically significant to the overall workspace satisfaction on their own, but their impacts becomes substantial when these IEQ variables are merged into larger environmental factors (i.e., Perceived Air Quality, Acoustics, Layout and Thermal). These results can support the development of an IEQ benchmarks for commercial buildings in Singapore. Graphical abstract: Image 1 Highlights: We conducted post-occupancy surveys in 7 commercial buildings in Singapore. 78% of respondents were satisfied with the overall workspace environment. Highest satisfaction: dress code, electrical lighting, and cleanliness. Highest dissatisfaction: sound privacy, personal control, and temperature. PAQ, Cleanliness and Acoustics greatly impact overall environment satisfaction.